Simultaneous three-wavelength depolarization measurements of clouds and aerosols using a coherent white light continuum - Somekawa, Toshihiro (Animo Repository, 2008)
Lidar (light detection and ranging) depolarization measurements were performed simultaneously at three wavelengths using a coherent white light continuum. The white light continuum ranging from the ultraviolet to the infrared region was generated by a focused 0.5 TW/100 fs pulse in a krypton gas cell at the atmospheric pressure. The lidar system consisted of three depolarization channels at 450, 550, and 800 nm. The observed depolarization ratios for each wavelength showed differences for clouds. These depolarization features in wavelength are discussed in terms of particle size and shape using T -matrix computations. The depolarization ratios at three wavelengths can be used to infer information on the size of the particles in clouds, assuming an ice crystal shape a priori. Also, the obtained size distributions from the three-wavelength depolarization ratios correspond with the changes in particle size indicated by changes in the Angstrom coefficient obtained by multiwavelength lidar techniques. This study demonstrated that the three-wavelength depolarization ratios provided additional information about the size and shape of clouds and aerosols. © 2008 American Institute of Physics.